Chronic Cocaine Administration Switches Corticotropin-Releasing Factor(2) Receptor-Mediated Depression to Facilitation of Glutamatergic Transmission in the Lateral Septum - Liu, Jie (J Neurosci, 2005)
Corticotropin-releasing factor (CRF) and urocortin (Ucn I) are endogenous members among a family of CRF-related peptides that activate two different and synaptically localized G-protein-coupled receptors, CRF(1) and CRF(2). These peptides and their receptors have been implicated in stress responses and stress with cocaine abuse. In this study, we observed significant alterations in excitatory transmission and CRF-related peptide regulation of excitatory transmission in the lateral septum mediolateral nucleus (LSMLN) after chronic cocaine administration. In brain slice recordings from the LSMLN of control (saline-treated) rats, glutamatergic synaptic transmission was facilitated by activation of CRF(1) receptors with CRF but was depressed after activation of CRF(2) receptors with Ucn I. After acute withdrawal from a chronic cocaine administration regimen, CRF(1) activation remained facilitatory, but CRF(2) activation facilitated rather than depressed LSMLN EPSCs. These alterations in CRF(2) effects occurred through both presynaptic and postsynaptic mechanisms. In saline-treated rats, CRF(1) and CRF(2) coupled predominantly to protein kinase A signaling pathways, whereas after cocaine withdrawal, protein kinase C activity was more prominent and likely contributed to the CRF(2)-mediated presynaptic facilitation. Neither CRF nor Ucn I altered monosynaptic GABA(A)-mediated IPSCs before or after chronic cocaine administration, suggesting that loss of GABA(A)-mediated inhibition could not account for the facilitation. This switch in polarity of Ucn I-mediated neuromodulation, from a negative to positive regulation of excitatory glutamatergic transmission after chronic cocaine administration, could generate an imbalance in the brain reward circuitry associated with the LSMLN.